Integrating HASSET Thesaurus with ICSSR Data Service - Pandya, Miteshkumar (Journal of Information and Knowledge, 2018)
This article studies effective use of thesaurus which provides access to wide range of subject keywords and pick right one which is best suited to describe the dataset being indexed. The article provides brief information on ICSSR Data Service followed by aims and objectives. It also elaborates need for the integrating thesaurus with a data input worksheet of the online databases. It also enlists steps of assigning subject keywords to a dataset being indexed in the repository.